Matrilineal Paradox in Semende and Minangkabau Culture - Arifin, Zainal (Komunitas, 2019)
Minangkabau and Semende are a community with a very strong matrilineal kinship system, where one of its characteristics is that power and control of resources are in the hands of women. Following their matrilineal system, decision making on property division (inheritance) is given to the eldest child, who in the case of Semende is called tunggu tubang. In the Minangkabau and Semende communities, the customary provision that places women as central power and control of resources ultimately generates a paradox. Traditionally, the power and control of resources are in the hands of women, but in empirical reality (social practice), these are controlled and supervised by the men in the community. Through ethnographic research methods, this paradox is understood by deeply investigating the knowledge structure of actors in these two societies about what and how these customs (adat) are understood and applied in their lives. The research findings show that the paradox is a result of the existence of ambiguous customary provisions, in which power and control of resources are handed over to women, but these provisions also open opportunities for men to take authority over matters. These customary provisions then spark male political movement to redefine these provisions in order to have power over matters as well. This suggests that in matrilineal societies or societies where women empowerment andÂ influences are dominant, the potential of men to strengthen their authority and control over matters tend to occur frequently, which ultimately lead to matrilineal paradox.